Political Instability, Economic Inequality and Social Conflict: The Case in Italy - Ippolito, Marzia; Cicatiello, Lorenzo (Panoeconomicus, 2019)
Rising economic inequality may produce a contraction of political stability and a spread of social conflict, as suggested by the theory of relative power. Following this approach, participation in the political arena depends on the distribution of incomes, because the relative rich use their power to ensure that the status quo do not change, while the relative poor are likely to abandon the public arena when they realize that their demands will not be discussed. Through the implementation of an index of political stability on the Italian general elections of 2008 and 2013, this study empirically tests whether political instability is linked with economic inequality. The results of the analysis, which examines the sub-regional level, show that the strengthening of economic inequality is a decisive factor affecting the weight of the elites in the determination of economic and political choices, and that it influences the distribution of votes between political blocks. This comes at the disadvantage of the poorest who, aware of their lesser chances to have influence, choose to change the character of their participation. Key words: Political participation, Social conflict, Relative power theory. JEL: D31, D72.Politička nestabilnost, ekonomska nejednakost i socijalni sukob: slučaj u ItalijiRastuća ekonomska nejednakost može proizvesti kontrakciju političke stabilnosti i širenje društvenih sukoba, kao što to sugeriše teorija relativne moći. Prateći ovaj pristup, učešće u političkoj sceni zavisi od raspodele prihoda, jer relativno bogati koriste svoju moć da osiguraju da se status quo ne promeni, dok će relativno siromašni verovatno napustiti javnu scenu kada shvate da se o njihovim zahtevima neće raspravljati. Kroz implementaciju indeksa političke stabilnosti na opštim izborima u Italiji 2008. i 2013. godine, ovaj rad empirijski testira da li je politička nestabilnost povezana sa ekonomskom nejednakošću. Rezultati analize, koja razmatra subregionalni nivo, pokazuju da je jačanje ekonomske nejednakosti odlučujući faktor koji utiče na ulogu elite u određivanju ekonomskih i političkih izbora, i da utiče na distribuciju glasova između političkih blokova. To je nepovoljno za najsiromašnije koji, svesni da imaju manju šansu da imaju uticaj, odlučuju da promene karakter svog učešća.Ključne reči: Politička participacija, društveni konflikt, teorija relativne moći.